MSCT imaging of various shunts and grafts in post operative cases of congenital heart diseases - Patel, Dinesh L.; Rana, Yashpal R.; Sheth, Megha M.; Patel, Samir G.; Garachh, Milin N.; Parikh, Kamal K. (International Journal of Research in Medical Sciences, 2019)
Background: Multi-slice computed tomography (MSCT) plays an important role in clinical practice in assessing post-operative patients with complex CHD when echocardiography is not contributory. Despite the great capabilities of MR imaging for anatomic and functional assessment of the heart, it is time-consuming and may require a lengthy period of patient sedation; hence its use in seriously ill or uncooperative patients is often limited. CT has the advantages of widespread availability and short acquisition times. It is imperative for a radiologist to be aware of various palliative as well as corrective procedures and their various imaging findings. Aim of this article is to demonstrate and make one aware of various checklists and imaging findings in paediatric patients who have undergone various shunts and grafts at our tertiary cardiac care centre, their immediate as well as long term complications. Methods: We studied a total of 100 paediatric patients (<12 years old), who had undergone some sort of palliative or corrective shunt or graft placement, on MSCT during the period 2014 to 2018 at our tertiary cardiac care centre. Results: We try to outline details of various shunts and grafts used in congenital heart diseases correction, MSCT technique and imaging appearances and appearances of abnormal post-operative findings. Conclusions: Advances in computed tomography (CT) scanners and electrocardiographic gating techniques have resulted in superior image quality of the aorta and pulmonary arteries for evaluating postoperative congenital heart disease. MSCT is an excellent non-invasive modality for post-operative evaluation of various shunts and grafts.